Acetaldehyde involvement in ethanol's postabsortive effects during early ontogeny - March, Samanta M.; Abate, Paula; Molina, Juan C. (Frontiers in Behavioral Neuroscience, 2013)
Clinical and biomedical studies sustains the notion that early ontogeny is a vulnerable window to the impact of alcohol. Experiences with the drug during these stages increase latter disposition to prefer, use or abuse ethanol. This period of enhanced sensitivity to ethanol is accompanied by a high rate of activity in the central catalase system, which metabolizes ethanol in the brain. Acetaldehyde (ACD), the first oxidation product of ethanol, has been found to share many neurobehavioral effects with the drug. Cumulative evidence supports this notion in models employing adults. Nevertheless very few studies have been conducted to analyze the role of acetaldehyde in ethanol postabsorptive effects, in newborns or infant rats. In this work we review recent experimental literature that syndicates ACD as a mediator agent of reinforcing aspects of ethanol, during early ontogenetic stages. We also show a meta-analytical correlational approach that propose how differential concentrations of central catalase across ontogeny, could be modulating patterns of ethanol affinity.